1990
DOI: 10.1038/bjc.1990.83
|View full text |Cite
|
Sign up to set email alerts
|

Crypt restricted heterogeneity of goblet cell mucus glycoprotein in histologically normal human colonic mucosa: a potential marker of somatic mutation

Abstract: Current evidence from experimental animals suggests that the colonic crypt is a clonal unit derived from, and maintained by, a single cell (Griffiths et al., 1988). Treatment of normal female TO strain mice with the colon-specific carcinogen dimethylhydrazine (DMH) results in a histochemically demonstrable loss of activity of the X-linked enzyme glucose-6-phosphate dehydrogenase (G6PD) in single, randomly distributed colonic crypts. This phenotypic change is uniform within the affected crypts, and its frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 5 publications
5
38
0
Order By: Relevance
“…2), suggesting that mutated crypts appear after birth and increase with age. This is in line with an earlier report by Fuller et al (7) in which the colonic mucosa of 18 infants and children revealed only two patterns of staining reaction, either uniformly negative or uniformly positive mPAS staining, indicating no demonstration of mutated crypts. This tendency would explain the increase in colorectal cancer development with age, (16) supporting multistep carcinogenesis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…2), suggesting that mutated crypts appear after birth and increase with age. This is in line with an earlier report by Fuller et al (7) in which the colonic mucosa of 18 infants and children revealed only two patterns of staining reaction, either uniformly negative or uniformly positive mPAS staining, indicating no demonstration of mutated crypts. This tendency would explain the increase in colorectal cancer development with age, (16) supporting multistep carcinogenesis.…”
Section: Discussionsupporting
confidence: 80%
“…This tendency would explain the increase in colorectal cancer development with age, (16) supporting multistep carcinogenesis. (4) According to the previous report, (7) no difference was found in the mutation frequencies of colonic crypts between age-matched individuals with sporadic colorectal cancer and benign colonic conditions. Therefore, it is worthwhile to see the age influence on mutation frequencies in the present study, although non-cancerous mucosa is not completely normal in cases with sporadic colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the crypt-restricted loss of ability to acylate O-sialomucin, the goblet cells in an entire single crypt stain positively with mild periodic acid Schiff (38), or negatively by the periodate-borohydride/potassium hydroxide saponification/periodic acid Schiff method which stains O-acetyl sialic acid residues (39). This crypt-restricted staining with mild periodic acid Schiff was observed after X-irradiation therapy for rectal cancer (31) (38).…”
Section: Discussionmentioning
confidence: 99%
“…This approach yields T pot , defined as the time between cell divisions in the absence of cell death. Several hundred colorectal cancers have been evaluated by this method, with T pot measured as Ϸ4 days (16)(17)(18)(19)(20)(21). By using this figure for the cell division rate and the mutational data reported in ref.…”
Section: Point Mutation Rates and Growth Kinetics Of Colorectal Cancersmentioning
confidence: 99%